Tsotsitaal and cultural identity : A sociolinguistic study of young black South African women who speak tsotsitaal. - Mmako, Maipato Caroline (University of the Witwatersrand, Johannesburg, 2024)
This study aimed to explore whether young black women identify with tsotsitaal as an integral aspect of their culture and personal identity. It covered background information, rationale, research questions, and objectives. Additionally, it delved into the origins of tsotsitaal and its significance in the lives of young people in township settings. A review of relevant literature highlighted a gap in understanding the role of women who speak tsotsitaal, prompting further investigation. Using a qualitative research approach, the study employed a questionnaire for data collection. The sample consisted of 20 young women aged 18 to 30 from Diepkloof (Soweto) and Katlehong (Vosloorus), with equal representation from both areas. Findings indicated that young black women indeed identify with tsotsitaal as part of their cultural identity, and some speak it independently of male influence. Moreover, the study revealed that speaking tsotsitaal is not necessarily associated with lack of education; rather, it is seen as a mode of expression and cultural belonging. Based on these findings, suggestions were made for future research to broaden its scope and conduct in-depth interviews with focus groups to better understand the role of tsotsitaal in shaping the identity of young women in townships. Despite its small sample size, the study provides valuable insights for researchers interested in further exploring this topic.
A research report Submitted in fulfillment of the requirements for a Master of Arts Degree by Coursework and Research Report in Sociology, In the Faculty of Humanities , School of Social Sciences, University of the Witwatersrand, Johannesburg, 2024
Keywords: Tsotsitaal; Culture; Identity; SDG-5: Gender equality